Liquid crystal electro-optical transducers for electrophysiology sensing applications. (1st October 2022) - Al Abed, Amr; Wei, Yuan; Almasri, Reem M; Lei, Xinyue; Wang, Han; Firth, Josiah; Chen, Yingge; Gouailhardou, Nathalie; Silvestri, Leonardo; Lehmann, Torsten; Ladouceur, François; Lovell, Nigel H
Abstract: Objective. Biomedical instrumentation and clinical systems for electrophysiology rely on electrodes and wires for sensing and transmission of bioelectric signals. However, this electronic approach constrains bandwidth, signal conditioning circuit designs, and the number of channels in invasive or miniature devices. This paper demonstrates an alternative approach using light to sense and transmit the electrophysiological signals. Approach. We develop a sensing, passive, fluorophore-free optrode based on the birefringence property of liquid crystals (LCs) operating at the microscale. Main results. We show that these optrodes can have the appropriate linearity ( µ ± s.d.: 99.4 ± 0.5%, n  = 11 devices), relative responsivity ( µ ± s.d.: 57 ± 12%V −1, n  = 5 devices), and bandwidth ( µ ± s.d.: 11.1 ± 0.7 kHz, n  = 7 devices) for transducing electrophysiology signals into the optical domain. We report capture of rabbit cardiac sinoatrial electrograms and stimulus-evoked compound action potentials from the rabbit sciatic nerve. We also demonstrate miniaturisation potential by fabricating multi-optrode arrays, by developing a process that automatically matches each transducer element area with that of its corresponding biological interface. Significance. Our method of employing LCs to convert bioelectric signals into the optical domain will pave the way for the deployment of high-bandwidth optical telecommunications techniques in ultra-miniature clinical diagnostic and research laboratory neural and cardiac interfaces.